Cross Sectional Study of Knowledge about MR (Measles Rubella) Campaign in Medical and Nursing Students Studying at Civil Hospital, Ahmedabad - Rajan K. Parmar; Hetal Y. Patel; Hely B. Patel; Rajshree J. Bhatt; Mitesh K. Patel (Indian Association of Preventive and Social Medicine, 2020)
Introduction : India is committed to goal of Measles elimination and Rubella control by 2020, for this purpose MR vaccination campaign has implemented. Objective: To assess awareness of MR Campaign in medical and nursing students of civil hospital, Ahmedabad. Methods: This cross sectional study was conducted on medical and nursing students of civil hospital, Ahmedabad, Gujarat. Baseline knowledge of MR campaign, side effects of MR vaccine, was assessed by a self-administered structured questionnaire. Data analysis was done in Microsoft excel and chi square test was applied. Results: There were 222 respondents and among them 120 (54%) were medical students and 102 (46%) were nursing students, with male female ratio of 95:127. Awareness regarding MR Vaccination Campaign found significantly more in nursing students as compare to medical students whereas Medical students had more knowledge about MR vaccine as compared to nursing students. Conclusion: There is still gap in awareness of MR vaccination campaign among medical students. Field visits among nursing students have positive effects on awareness of nursing students.